A research agenda for a human rights centred criminology - Weber, Leanne (Palgrave critical studies in human rights and criminology, 2024)
Chapter 1. Introduction: A research agenda for a human rights centred criminology(Leanne Weber and Marinella Marmo) -- Chapter 2. Criminological research for human rights (Elizabeth Stanley) -- Chapter 3. Speaking rights to power or governing through rights?: Making rights matter in the security field (Claire Hamilton) -- Chapter 4. Researching policing from the perspective of the policed: studying human rights from below (Will Jackson) -- Chapter 5. Criminology, humanitarianism, and the right to life at the border (Katja Franko) -- Chapter 6. The promise and pitfalls of human rights in immigration detention (Mary Bosworth and Andriani Fili) -- Chapter 7. An anticolonial, abolitionist, and feminist lens to interrogate human rights penalty (Silvana Tapia Tapia) -- Chapter 8. Human rights for Southern Criminology: Neoliberal colonialism and rights from below (Pablo Ciocchini and Joe Greener) -- Chapter 9. Actioning the Human Rights Agenda and Issues of Access to Justice (Danielle Watson, Julie Berg and Lamese Laponi) -- Chapter 10. Developing a kaupapa Māori rights-focused research agenda (Stella Black, Dave Burnside, Jess Hastings, and Katey Thom) -- Chapter 11. Queer Criminology through the Lens of the Global South and its Impact on Human Rights (George B. Radics).-Chapter 12. Are victim stories human rights stories? Towards an ethics and politics of listening and seeing for victimology (Sandra Walklate) -- Chapter 13. Gendered violence: A human rights agenda for criminology (Nancy A. Wonders and Sydney Shevat) -- Chapter 14. Towards a Human Rights Criminology of Public Health (Raymond Michalowski and Rebecca Annorbah) -- Chapter 15. Carceral Spaces and OPCAT: resisting the temptation of human rights? (Claire Loughnan and Steven Caruana) .